Analisis Minat Investasi Mahasiswa dalam Perspektif Theory of Reasoned Action (Studi Kasus Pada Mahasiswa Program Studi Akuntansi Fakultas Ekonomi, Bisnis dan Pariwisata Universitas Hindu Indonesia) - Dewa Ayu Komang Gangga Sandy Dewi; I Wayan Sudiana; Ni Made Wisni Arie Pramuki (UNHI Press, 2025)
Investment interest is an individual's desire or interest to invest without any compulsion with the aim of obtaining future profits. The low investment interest among students needs to be considered because investment is one of the driving factors for a country's economic growth. This study aims to examine empirically the effect of attitudes and subjective norms on investment interest of students of the Accounting Study Program, Faculty of Economics, Business and Tourism, Universitas Hindu Indonesia. The populatiion in thiis study were students off the Accounting Studiy Program, Faculty of Economiics, Business and Tourism, Universitas Hindu Indonesia, Class of 2020 and 2021. The number of samples in this study were 183 respondents determined by stratified random sampling technique. Data collection was carried out using a questionnaire and tested using Partial Least Squares (PLS) analysis techniques. The results showed that attitudes and subjective norms had a significant positive effect on the investment interest of students of the Accounting Study Program, Faculty of Economics, Business and Tourism, Universitas Hindu Indonesia.